An Analysis of Student Ability in Understanding Noun Clause and Its Function: A Study of Student English Department in Academic Year 2018 at UNP - Ranti Melantari; Sitti Fatimah (Universitas Negeri Padang, 2020)
This study was students’ ability in understanding noun clause and its function: a study of students’ English department at UNP. The type of this research was descriptive quantitative research. According to the result of the research, the mean score of the students was 61.76. the students’ abilities in understanding noun clause and its function that had 2 students or 8% were included in the highest score or having excellent level. 8 students or 32% students were included in good level. Then, 10 students or 40% were included in fair level, 4 students or 10% students were included in poor level and 1 students or 4% students were included in very poor level. It shows that the students’ ability in understanding noun clause and its function of the students’ English language and literature department in academic year 2018 at UNP had fair level by mean score 61.76. They also do not master the concept of noun clause and how to use the noun clause itself in a sentence, and also they never practicing of the use of noun clause and its function well.